Mass-Migration to the Western World in Light of the Hebrew Bible The Challenge of Complexity - Zehnder, Markus 1964- (2018)
The present study deals with two distinct aspects of the biblical views of migration: 1) What are some of the salient distinctions that are made within the biblical material concerning various types of "foreigners"? 2) What does the complex web of traditions concerning ethnic and religious "otherness" and various kinds of migration within the Hebrew Bible look like? The concepts of nokri and ger, different types of foreigners living in Israel, are analysed in detail. At the end some of the main aspects of migration in New Testament texts, especially as they relate to the Hebrew Bible, will be presented. The observations adduced in these three sections can contribute to shed some kind of "biblical light" on the analysis and discussion of the current situation in Western countries, where large numbers of people attempt to reach their shores and settle within their borders.
Keywords: Bible. Deuteronomy; Emigration & Immigration; Ethics; Jesus Christ; Theology